Spatiotemporal evaluation of biomass burning emissions in Equatorial Southeast Asia (ESEA) for 2013 and 2021 - Chin, Jia Hui; Justin Sentian; Hian, Jackson Wui Chang; Farrah Anis Fazliatul Adnan; Salwa Naidin; Franky Herman; Teo, Yu Rou (AAGR Aerosol and Air Quality Research, 2025)
Equatorial Southeast Asia (ESEA) is crucial to global climate dynamics, particularly during El Niño events, which greatly enhance biomass burning activities and lead to significant declines in air quality. The fire activity within this region is intricately linked to the phases of the El Niño-Southern Oscillation (ENSO) and the prevailing regional monsoon patterns, both of which dictate the frequency and intensity of biomass burning events. However, there is a concerning absence of comprehensive inventories detailing these emissions in ESEA. This data shortfall limits our understanding of the full impact of biomass burning on local and global scales, underscoring the pressing need for enhanced emissions inventory initiatives in the region. This study seeks to evaluate biomass burning emissions specifically for the non-El Niño years of 2013 and 2021 through a bottom-up approach. To analyze land cover distribution and identify burned areas throughout ESEA, we utilized remote sensing data from MODIS alongside geospatial analysis tools. Emission estimates were derived by multiplying the burned land area (in km2) by combustion factors (CF), fuel loading (FL), and emission factors (EF) sourced from existing literature. Our findings illustrate a stark contrast in total emissions, with 2013 generating a significantly higher total of 7,289,220.68 Mg compared to 1,536,779.55 Mg in 2021. Both years exhibited a bi-modal emission pattern, reflective of the equatorial precipitation regime, which produces two distinct dry seasons. The primary emission species identified were carbon dioxide ( CO2), followed by carbon monoxide (CO) and non-methane volatile organic compounds (NMVOCs), with shrublands and evergreen forests acting as significant contributors. Notably, Sumatra and Kalimantan emerged as key emission hotspots in this analysis.